Investigation of Physical and Mechanical Properties of Locally Available Aggregates with Different Combination for Pavement - Ron Aldrino, Chan@Ron Buking; Mahathir, Mohd Noor; Ervin Rangga, Edwin; Wan Hashim, Wan Ibrahim (Springer Nature Singapore Pte Ltd., 2022)
The objectives of this research is to examine as to how wetting and drying cycles affect the mechanical properties of different granite, limestone, and microtonalite aggregate combinations. Throughout this study, the physical and mechanical properties of granite, limestone and microtonalite aggregates are studied using granite as the main aggregates in a variety of combination designs. Limestone and microtonalite aggregates are chosen for the modified aggregates as they may be used in the combination aggregate design to reduce the use of granite aggregates in the industry. Laboratory work on the Elongation Index Test and Specific Gravity to determine the physical properties of aggregates was performed at the first phase of laboratory testing. In the second phase of the laboratory, the aggregate combination was tested with Aggregate Impact Value (AIV), Aggregate Crushing Value (ACV) and Los Angeles Abrasion (LAA) to assess their mechanical properties. The value for granite, limestone and microtonalite aggregates for both controlled and wetting and drying samples for AIV, ACV and LAA has met the standard requirement for Public Work Department, Malaysia, which is not more than 25% for AIV, not more than 30 % for ACV and not more than 45% for LAA, respectively. The result thus concludes that the combination of granite, limestone and microtonalite aggregates is acceptable and has the potential to be used in the industry.